2014
DOI: 10.1080/14685248.2014.932364
|View full text |Cite
|
Sign up to set email alerts
|

Rotating turbulent Rayleigh–Bénard convection subject to harmonically forced flow reversals

Abstract: The characteristics of turbulent flow in a cylindrical Rayleigh-Bénard convection cell which can be modified considerably in case rotation is included in the dynamics. By incorporating the additional effects of an Euler force, i.e., effects induced by nonconstant rotation rates, a remarkably strong intensification of the heat transfer efficiency can be achieved. We consider turbulent convection at Rayleigh number Ra = 10 9 and Prandtl number σ = 6.4 under a harmonically varying rotation, allowing complete reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…While there exists a body of previous research works, both experimental and numerical, on RB convection with timedependent rotation, such works have mostly focused on non-turbulent states [42][43][44][45][46]. Recently, however, DNS studies [47,48] and an exploratory experimental study [49] have shown potentially significant effects of modulated rotation on heat transport in turbulent RB convection.…”
Section: Introductionmentioning
confidence: 99%
“…While there exists a body of previous research works, both experimental and numerical, on RB convection with timedependent rotation, such works have mostly focused on non-turbulent states [42][43][44][45][46]. Recently, however, DNS studies [47,48] and an exploratory experimental study [49] have shown potentially significant effects of modulated rotation on heat transport in turbulent RB convection.…”
Section: Introductionmentioning
confidence: 99%